Representation of the moderate education curriculum in Indonesia; integration of NU and Muhammadiyah thought - Sumiarti; Azizah, Intan Nur (ATTARBIYAH: Journal of Islamic Culture and Education, 2024)
This study aims to analyze the curricula of NU and Muhammadiyah educational institutions, focusing on their contributions to supporting moderate Islamic education. The research was conducted in Central Java, Indonesia, using a descriptive qualitative method. Data collection techniques included classroom observations, in-depth interviews with school principals and teachers, as well as an analysis of curriculum documents and teaching materials. The findings reveal fundamental differences and similarities between the two curricula. NU's curriculum is rooted in the concept of "Islam Nusantara," emphasizing the integration of Islamic teachings with local culture and national identity, fostering harmony with state principles such as Pancasila and Bhinneka Tunggal Ika. Meanwhile, Muhammadiyah's curriculum is based on the concept of "Progressive Islam," prioritizing modernity and incorporating contemporary sciences and social issues into the educational framework. This comparative analysis concludes that both educational institutions significantly contribute to shaping moderate Islamic perspectives through their curricula. The NU curriculum focuses on cultural preservation and religious harmony, while the Muhammadiyah curriculum emphasizes innovation and progress, aligning Islamic education with modern global challenges. This study highlights the potential of these curricula as frameworks to address socio-religious challenges, foster peace, and counter radicalism in Indonesia.